Prognostic Value of Endothelial Progenitor Cells in Acute Myocardial Infarction Patients - Gongjie Ye; Xiaodan Chen; Yinchao Zhou; Jianqing Zhou; Yongfei Song; Xiaoyong Yang; Lei Yang (Hindawi Limited, 2023)
Objective. To determine prognostic role of endothelial progenitor cells (EPCs) in intensive care patients with acute myocardial infarction (AMI). Materials and Methods. From December 2018 to July 2021, a total of 91 eligible patients with AMI were consecutively examined in a single intensive care unit (ICU) in China. Patients with a history of acute coronary artery disease were excluded from the study. Samples were collected within 24 hr of onset of symptoms. EPCs, defined as coexpression of CD34+/CD133+ cells or CD133+/CD34+/KDR+, were studied using flow cytometry and categorized by quartiles. Based on the 28-days mortality outcome, the patients were further divided into two groups: death and survival. The study incorporated various variables, including cardiovascular risk factors such as body mass index, hypertension, diabetes, hypercholesterolemia, atherosclerotic burden, and medication history, as well as clinical characteristics such as APACHEⅡscore, central venous-arterial carbon dioxide difference (GAP), homocysteine, creatinine, C-reactive protein, HbAlc, and cardiac index. Cox regression analysis was employed to conduct a multivariate analysis. Results. A total of 91 patients with AMI who were admitted to the ICU were deemed eligible for inclusion in the study. Among these patients, 23 (25.3%) died from various causes during the follow-up period. The counts of EPCs were found to be significantly higher in the survival group compared to the death group (P<0.05). In the univariate analysis, it was observed that the 28-days mortality rate was associated with the several factors, including the APACHEⅡscore (P=0.00), vasoactive inotropic score (P=0.03), GAP (P=0.00), HCY (P=0.00), creatinine (P=0.00), C-reactive protein (P=0.00), HbAlc (P=0.00), CI (P=0.01), quartiles of CD34+/CD133+ cells (P=0.00), and quartiles of CD34+/CD133+/KDR+ cells (P=0.00). CD34+/CD133+/KDR+ cells retained statistical significance in Cox regression models even after controlling for clinical variables (HR: 6.258 × 10−10 and P=0.001). Nevertheless, no significant correlation was observed between CD34+/CD133+ cells and all-cause mortality. Conclusions. The decreased EPCs levels, especially for CD34+/CD133+/KDR+ cells subsets, were an independent risk factor for 28-days mortality in AMI patients.